Fundamental Metrics for Wireless Sensor Networks localization - Javad Rezazadeh; Marjan Moradi; Abdul Samad Ismail (Institute of Advanced Engineering and Science, 2012)
During the last decade, Localization in wireless sensor networks (WSNs) is a broad topic that has received considerable attention from the research community. The approaches suggested to estimate location are implemented with different concepts, functionalities, scopes and technologies. This paper introduces a methodological approach to the evaluation of localization algorithms and contains a discussion of evaluation criteria and performance metrics followed by statistical/ empirical simulation models and metrics that affect the performance of the algorithms and hence their assessment. The major contribution of this paper is to analyze and identify relevant metrics to compare different approaches on the evaluation of localization schemes.DOI:http://dx.doi.org/10.11591/ijece.v2i4.247